Market Encounters : Consumer Cultures in Twentieth-Century Ghana - Murillo, Bianca; Murillo, Bianca (Book collections on Project MUSE., 2017)
By emphasizing the centrality of human relationships to Ghana's economic past, Murillo introduces a radical rethinking of consumption studies from an Africa-centered perspective. The result is a keen look at colonial capitalism in all of its intricacies, legacies, and contradictions, including its entanglement with gender and race.